2008
DOI: 10.2478/s11756-008-0145-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antibiotics on cell proliferation in the Closterium peracerosum-strigosum-littorale complex (Charophyceae, Chlorophyta)

Abstract: Abstract:The effects of several antibiotics on the proliferation of cells of the Closterium peracerosum-strigosum-littorale complex, a unicellular charophycean alga, were examined. When cells were cultured on solid medium containing hygromycin B and phleomycin the proliferation of cells was inhibited at low concentrations of these antibiotics, with a minimum inhibitory concentration of 5.0 and 0.2 µg/mL, respectively. By contrast, kanamycin sulfate was less effective at concentrations up to 50 µg/mL. When cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…To obtain stable transformants, we incubated the electroporated cells in the presence of hygromycin (10 µg ml –1 ). We previously demonstrated that wild‐type C. psl complex cells cannot proliferate in hygromycin (5 μg ml –1 ) (Abe et al ., 2008b). Here, no surviving cells were observed when 1 × 10 4 nonelectroporated control cells were incubated in 5 or 10 μg ml –1 hygromycin for 14 d. After 3 wk of selection, a number of surviving cells were obtained.…”
Section: Resultsmentioning
confidence: 99%
“…To obtain stable transformants, we incubated the electroporated cells in the presence of hygromycin (10 µg ml –1 ). We previously demonstrated that wild‐type C. psl complex cells cannot proliferate in hygromycin (5 μg ml –1 ) (Abe et al ., 2008b). Here, no surviving cells were observed when 1 × 10 4 nonelectroporated control cells were incubated in 5 or 10 μg ml –1 hygromycin for 14 d. After 3 wk of selection, a number of surviving cells were obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Phleomycin is a useful antibiotic for the selection of stable transformants in the C. psl. complex because the drug inhibits cell proliferation at low concentrations both in liquid media and on solid media (Abe et al 2008b ). The overexpression vector pSA1102, which allowed direct selection by phleomycin and the overexpression of the arbitrary genes, was constructed (Fig.…”
Section: Genetic Transformationmentioning
confidence: 99%